Megaliths of the world. - Laporte, Luc; Large, Jean-Marc, 1955-; Nespoulous, Laurent; Scarre, Christopher; Steimer-Herbet, Tara (Archaeopress Publishing Ltd, 2022)
Bringing together the latest research on megalithic monuments throughout the world, 150 researchers offer 72 articles, providing a region-by region account in their specialist areas, and a summary of the current state of knowledge. Highlighting salient themes, the book is vital to anyone interested in the phenomenon of megalithic monumentality.